2022
DOI: 10.1590/fst.107321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subcritical water extraction and cultivar geographical location on the phenolic compounds and antioxidant capacity of Quebranta (Vitis vinifera) grape seeds from the Peruvian pisco industry by-product

Abstract: The objectives of this study were to evaluate the effects of the grape cultivar geographical location and extraction technique on the total phenolic compounds (TPC), antioxidant capacity (AC), oil yield and quality of Quebranta (Vitis vinifera) grape seeds. Seeds were defatted with supercritical CO 2 and the bioactive compounds were extracted with subcritical water and macerations with methanol, ethanol, and acetone. The differences in grape seed oil yield were not significant (p > 0.05). The most abundant fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Extensive research has examined the various environmental effects on wine grapes and their polyphenolic content [ 26 , 27 , 28 , 29 , 30 ]. However, table grapes have received comparatively less attention, with only a few studies exploring their susceptibility to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has examined the various environmental effects on wine grapes and their polyphenolic content [ 26 , 27 , 28 , 29 , 30 ]. However, table grapes have received comparatively less attention, with only a few studies exploring their susceptibility to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Pedras et al [ 100 ] postulated that the liberation of polyphenols inside the matrix of spent coffee grounds and the potential conversion of lignin into polyphenols could explain this observed enhancement. Previous studies have documented comparable investigations on the SWE of phenolics from sorghum bran [ 91 ], defatted cake and coffee powder [ 101 ], yarrow byproducts [ 102 ], onion skin [ 103 ], Hayward kiwifruit pomace [ 104 ], papaya seeds [ 105 ], grape seeds [ 106 ], spent coffee grounds [ 107 ] and chestnut shells [ 108 ].…”
Section: Thermal Extraction Methodsmentioning
confidence: 99%
“…In particular, it was found that red grape pomace had a higher antioxidant power than white grape pomace when added to the formulations of spreadable cheese and Primosale [ 14 , 54 ]. Barriga-sánchez et al [ 78 ] analyzed the antioxidant activity of Quebranta grape seeds from three different geographical areas and the results showed that seeds from zones A (167.56 ± 10.40 mg GAE/g DW and 1479.90 ± 12.86 µmol TE/g DW) and B (161.83 ± 4.95 mg GAE/g DW and 1628.15 ± 80.32 µmol TE/g DW) had higher polyphenol contents and antioxidant activities compared to those from zone C (147.63 ± 16.18 mg GAE/g DW and 1167.92 ± 106.17 µmol TE/g DW).…”
Section: Functional Properties For Cheesemakingmentioning
confidence: 99%